Penggunaan Alat Musik Perkusi dalam Meningkatkan Kemampuan Motorik Kasar pada Anak Cerebral Palsy di SLB YPAC Makassar - Ariyandi, Yuzril; Hadis, Abdul; Meidina, Tatiana (JURNAL ORTO DIDAKTIKA, 2025)
This research examines gross motor skills in cerebral students palsy at SLB YPAC Makassar. The problems studied in this research is low gross motor skills in cerebral palsy students. As for the problem formulation that the author raises is